If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4(x + 3) = 36 Reorder the terms: 2x + 4(3 + x) = 36 2x + (3 * 4 + x * 4) = 36 2x + (12 + 4x) = 36 Reorder the terms: 12 + 2x + 4x = 36 Combine like terms: 2x + 4x = 6x 12 + 6x = 36 Solving 12 + 6x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6x = 36 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = 36 + -12 6x = 36 + -12 Combine like terms: 36 + -12 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 4e^3x+6=30 | | -3x-3x=26-2 | | 8c-13=3c+36 | | 2u^2-3u=0 | | -9=k-5k+7 | | 4x^2-15=25 | | 6t+17-3t=38 | | -6w+14=-76 | | 11x+22x-2y+54y= | | 0.5a-5-0.5a= | | -f^2+5f=0 | | 3-8p=29 | | 6(x+3)-9(x-1)=5-(X+3) | | 6t+17-3r=38 | | n-2n=n-4 | | 7r^2-5=0 | | G+14.8=45 | | 4x-2y=1forsubjecty | | 6(h-5+7)=2h+52 | | 6-16=-2z | | 60x=210 | | Y^2-15=3y+25 | | 4x+5y=841 | | -5x+-15x=-30 | | 4(t+8)-35= | | -3(f-4)=36 | | 47-(7)2= | | 7w-9x=2w+3x | | (5x-10)+(x+1)=180 | | 4(6y+3)-16y=52 | | X(.10)=1375 | | -3x+8y=-38 |